STRATEGI PEMANFAATAN PERAIRAN BAGI PENGEMBANGAN PERIKANAN BUDIDAYA DI KAWASAN TELUK STARING KABUPATEN KONAWE SELATAN - Akhmad Mansyur; Abdul Rahman (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2017)
This study aims to get the strategy that right and prioritize environmental, social and economic of utilization space Staring Gulf  waters in South Konawe  for the development of sustainable aquaculture. The experiment was conducted use a survey method in collecting primary and secondary data. To formulate the strategy of the company based on SWOT analysis is based on the logic to maximize strengths and opportunities, but at the same time to minimize the weaknesses and threats.  As a result, there are four strategies of utilization Staring Gulf waters for the development of sustainable aquaculture. First, restricted cultivation areas in a natural conservation area, especially for use in the delineation of seed lobsters that were backed up institusional and community empowerment. Second, policy enforcement from local authorities or the authorities to control the conversion of seed delineation region lobster in top down (policy firm) through socialization and the provision of incentives and dis incentives for the offenders. Third, provide a special space allocation for security and protection of the coast, especially areas that often become transit and unloading of trade and the shipping lanes. Fourth, make a special safety area delineation region lobster and conservation seedlings are naturally the coast especially as sedimentation control measures, erosion and accretion.